Do Species Want to Evolve? - Turner, J. Scott (Filozoficzne Aspekty Genezy, 2022)
Darwinism, in all its various forms, seeks to explain evolution without the intervention of intelligence, purposefulness or intentionality: in short, via the abolition of purpose. Yet life is arguably a profoundly purposeful phenomenon, most evident in the phenomenon of adaptation. Modern Darwinism fails because it has no coherent theory of adaptation, and hence no coherent theory of life. Without this, it cannot claim to be a coherent theory of evolution. Here, I argue that a coherent theory of evolution will arrive when the inherent purposefulness of life can be reincorporated into our evolutionary thinking. Life’s fundamental property of homeostasis, coupled with the expanding conception of hereditary memory emerging from epigenetics and niche construction theory, can credibly restore purpose to our thinking about evolution. The evolution of lineages will no longer then be under the control of natural selection, but rather imbued with striving and intentionality: with “wanting” to evolve.